Medición de la circunferencia de la cadera y su relaciónen el desarrollo del hígado graso en el personal administrativo que presente obesidad abdominal de la unach periodo enero – junio 2011 - Paguay, Maricruz (2011)
Hepatic steatosis, also known as fatty liver is a liver disease characterized by theaccumulation of fatty acids and triglycerides in liver cells. The word comes from the term steatosis "steato" which sig ¬ fat quick explanation, and "osis" pathological process, ie, is the abnormal accumulation of fat inside their causes, there are two large groups, alcoholic and nonalcoholic.